Application of Group Counselling Guidance with the Anactive Mastery Experience Technique to Improve Self-Efficacy - Rezky Fathiyah Putri Aspar; Nadhirotul Laily (Global Action and Education for Society, 2025)
This study aims to examine the effectiveness of group counseling using the enactive mastery experience technique in improving students' self-efficacy in career decision making. The research was conducted at SMA X involving six students aged 17-18 years with low self-efficacy levels. The study applied a quasi- experimental approach with pre-test and post-test design using the Career Decision- Making Self-Efficacy (CDMSE) scale adapted from Purnama and Ernawati (2021). The intervention consisted of four group counseling stages: formation, transition, activity, and termination. The results showed a significant increase in students' self-efficacy from a mean score of 31.5 (low category) in the pre-test to 46.83 (high category) in the post-test. These findings indicate that group counseling with enactive mastery experience techniques effectively enhances students' confidence in recognizing their potential, setting career goals, and planning future education and work paths. This research suggests that group counseling can be an effective strategy for strengthening career decision-making skills among high school students.